A novel approach for detecting and recognizing mathematical symbols - Jahan, Nusrat; Nafiz, Mirza Abdullah Al (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.